Effects of alkali metal ion on imprinting GRIN microstructure in GeS2-Ga2S3-MCl (M=Na, K, Cs) glasses for visible to mid-infrared microgratings. Issue 22 (15th November 2022) - Liu, Bin; Mo, Yaoyao; Liu, Yongwei; Lu, Yunjun; He, Xiaoyan; Xu, Yinsheng; Lipovskii, Andrey; Yang, Guang
Abstract: Gradient refractive index (GRIN) micro-optics present unique opportunities for control of the chromatic properties, new degrees of freedom for optical design as well as the potential for use in new optical system applications. GRIN microgratings were imprinted in GeS2 -Ga2 S3 -MCl (M = Na, K, Cs) chalcohalide glasses by microthermal poling, and the effects of the type and concentration of alkali cations on their performance were investigated. Two effective imprinting formation regions of the GRIN microstructure based on the poling saturation voltage (Us ) and glass composition are observed at fixed poling time and temperature. The Us increases from 140 to 750 and 2600 V in accordance with the activation energy (Ea ) of alkali ions (Na + to K + and Cs + ) increasing from 45.15 to 58.62 and 92.58 kJ/mol for studied samples. The saturated numbers of diffraction order (Ns ) of the gratings in these samples are 7, 9 and 6, respectively, the highest number being provided by the K + -containing sample. This is in accordance with imprinting-induced phase differences (0.14λ, 0.19λ and 0.09λ) measured in the fabricated samples containing Na +, K + and Cs + ions. Furthermore, the Us of samples decreases from 1500 to 300 V with four concentrations of K + from 10 to 30%, associated with their Ea of K + decreasing from 69.62 to 53.46 kJ/mol, while Ns increases from 8 to 14, which is attributed to the increase of the phase difference in the GRIN structures. The controllable GRIN microstructures are realized by adjusting the type and concentration of alkali cations in chalcohalide glasses, which is expected to drive the design of broadband GRIN microgratings.